THE EFFECT OF MODEL PROBLEM BASED LEARNING (PBL) - Safrina Safrina; Saminan Saminan (SCAD Independent, 2015)
This study aims to determine the effect of the application of PBL models of science process skills (PPP) and the understanding of the concept of chemical substances in food at eighth grade students MTsN Meureudu. This study is a descriptive study using the research design one group pretest and posttest design. Samples were 19 eighth grade students MTsN Meureudu school year 2013/2014. Data collected by pretest and posttest to determine the effect of the application of PBL models and observation sheets to determine the feasibility of learning. The results showed that affects the application of PBL model of PPP and understanding the concept of chemical substances in food MTsN Meureudu eighth grade students. The influence can be seen from the results of hypothesis testing, the value is significantly smaller than α (0.05). In addition, the ability of a class VIII student representation MTsN Meureudu after application of PBL models on chemical substances in food material for the better. The ability of the student representation on enactive is 74%, 63% iconic, and symbolic 68%.